2017
DOI: 10.1002/cptc.201700034
|View full text |Cite
|
Sign up to set email alerts
|

Decarboxylative Alkynylation of Biomass‐Derived Compounds by Metal‐Free Visible Light Photocatalysis

Abstract: A mild method for decarboxylative C−C bond formation between natural carboxylic acids and alkynes is reported. Activation of a very broad scope of carboxylic acids derived from renewable resources is achieved by esterification to N‐(acyloxy)phthalimides. The cross‐coupling with acetylenic sulfones proceeds under irradiation with green light (528 nm) in the presence of the organic photocatalyst eosin Y and provides a metal‐free, environmentally friendly and inexpensive alternative to known decarboxylative alkyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…In this report, the authors demonstrated that NHPI esters generated in situ from a carboxylic acid yielded the desired products in slightly lower yields (Scheme 98). [114] …”
Section: C(sp3)−c(sp) Bond Formationmentioning
confidence: 99%
“…In this report, the authors demonstrated that NHPI esters generated in situ from a carboxylic acid yielded the desired products in slightly lower yields (Scheme 98). [114] …”
Section: C(sp3)−c(sp) Bond Formationmentioning
confidence: 99%
“…Using the same approach, Fu reported in 2016 the functionalization of side chains for the synthesis of chiral unnatural amino acids 62. Later König and coworkers improved the reaction of Chen by using Eosin Y as a replacement of Ru(bpy) 3 2+ 63. In 2016, Fu and coworkers harnessed the radical fragmentation of N -phthalimidoyl oxalates, first introduced by Overman,64 for the preparation of alkynylated quaternary centers (eqn (2)) 65.…”
Section: The Photoredox Catalysis Revolutionmentioning
confidence: 99%
“…This alkylation reaction had good chemical selectivity and functional group compatibility, which should be an environmentally friendly and inexpensive alternative procedure for the decarboxylative alkynylations. [140] Although redox-active NHP esters have been well developed as effective alkylation sources, their application in the absence of metals, as C-centered radical precursors, has been rarely reported in cyclization. In 2018, Guo's group [141] described an elegant metal-free cyclization reaction of NHP esters 1 with vinyl azides 64 with 15 W CFL irradiation for the synthesis of the important alkaloids 6alkylated phenanthridines 65 (Scheme 33a).…”
Section: Reactions Involving Eosin Y (Ey)mentioning
confidence: 99%